A two-level decision making approach for optimal integrated urban water and energy management. (15th July 2018) - Vakilifard, Negar; A. Bahri, Parisa; Anda, Martin; Ho, Goen
Abstract: A spatial-temporal model is proposed for optimal integrated water and energy resource management in urban areas, considering daily surplus output from residential grid-connected rooftop photovoltaics as an energy source for sustainable supply. The model addresses optimal investment and operational decisions of a desalination-based water supply system driven by surplus photovoltaic output and grid electricity. The two-level mixed integer linear programming model considers demands, systems configuration, resources capacity and electricity tariffs and gives the solution such that the highest compatibility with available renewable energy is achieved. The model is then applied to Perth, Australia and solved for three operational scenarios. The results show, for a given year, hourly (flexible) basis scenario leads to 9 521 425 and 18 673 545 economic benefits over seasonal (semi-flexible) and yearly (fixed) basis scenarios, respectively. They also indicate 19.9% better economic performance in terms of annualised unit cost of water production over existing Southern seawater desalination plant in Perth. Additionally, it is shown that the seasonal change on the optimal solutions mainly corresponds to the share of each energy resource to meet water-related energy demand. Finally, the results indicate higher sensitivity to the variation of the photovoltaic installation density compared to financial rate. Highlights: Surplus output from grid-connected photovoltaics is applied for urban water supply. A two-level optimisation model is used for investment and operational decisions. The spatial aspect of the problem is taken into account. Operational scenarios analysis is conducted for water and energy supply to Perth. Sensitivity analysis is done towards photovoltaic installations and financial rates.